THE CHANGE OF DIFFUSION PROCESSES FOR O+ + N2 ? NO+ + N REACTION IN THE IONOSPHERIC F REGION DURING THE SOLAR ECLIPSE OVER KHARKOV - Yasar, Mehmet (Vinca Inst Nuclear Sci, 2021)
Research on solar eclipses has been a very importance in detecting short and medium-scale changes in the ionosphere. In this paper, the relationship between the changes in self-diffusion coefficients of the O+ + N-2 -> NO+ + N reaction with the solar eclipse of March 29th, 2006 in Kharkov, Ukraine (49.6 degrees N and 36.3 degrees E) was investigated for 202, 252, and 303 km. The results of the research showed that self-diffusion coefficients increases with the increase of ionospheric altitude in each three days and the maximum diffusion value is reached at 303 km on 29th of March. It can be said that results of effects of solar eclipse in Turkey on ionosphere, results of the study of the experimental measurement and obtaining results of our study are consistent with one another.
Keywords: ionosphere; chemical processes; Kharkov incoherent scatter radar; solar eclipse; diffusion